THE EFFECT OF WORKLOAD, INDIVIDUAL CHARACTERISTICS, AND SCHOOL CLIMATE ON TEACHERS’ EMOTIONAL EXHAUSTION IN ELEMENTARY SCHOOLS OF PAPUA - Basilius Redan Werang (Jurnal Cakrawala Pendidikan, 2018)
Abstract:This study was aimed to investigate the potential effect of workload, individual characteristics, and school climate on teachers’ emotional exhaustion in Christian elementary schools of Boven Digoel district, Papua. The problems guided the study, namely: (a) does workloadeffectsignificant positively on teachers’ emotional exhaustion elementary schools?; (b) does individual characteristics effectsignificant positively on teachers’ emotional exhaustion in elementary schools?; and (c) does school climate effect significant positively on teachers’ emotional exhaustion in elementary schools?. Four quantitative questionnaires using Likert’s scale were administered to 94 teachers who have been decided as respondents. Data were analyzed quantitatively using simple linear regression analysis technique by employing SPSS version 21 for windows. Results of the study revealed that workload, individual characteristics, and school climate partially effect significant positively on teachers’ emotional exhaustion in elementary schools. These findings might be worthwhile for the school supervisors as well as The Head of Education Office in regional government level to eliminate teachers emotional exhaustion by creating different programs to improve workload system and to improve school climate on one hand and, on the other hand, to foster teachers’ character of hard-working.Keywords: workload, individual characteristics, school climate, emotional exhaustion, teachers PENGARUH BEBAN KERJA, KARAKTERISTIK INDIVIDU, DAN IKLIM SEKOLAH TERHADAP KELELAHAN EMOSIONAL GURU SD DI PAPUAAbstrak: Tujuan penelitian ini adalah untuk menginvestigasi pengaruh beban kerja, karakteristik individu,  dan iklim sekolah terhadap kelelahan emosional guru SD Kristen di Kabupaten Boven Digoel, Papua. Masalah yang menuntun penelitian ini adalah: (a) apakah beban kerja guru berpengaruh secara positif dan signifikan terhadap kelelahan emosional guru SD?; (b) apakah karakteristik individu berpengaruh secara positif dan signifikan terhadap kelelahan emosional guru SD?; dan (c) apakah iklim sekolah berpengaruh secara positif dan signifikan terhadap kelelahan emosional guru SD? Empat angket kuantitatif yang menggunakan Skala Likert disebarkan kepada 94 guru yang menjadi responden. Data dianalisis secara kuantitatif menggunakan SPSS versi 21. Hasil analisis data menunjukkan bahwa beban kerja, karakteristik individu, dan iklim sekolah secara parsial berpengaruh secara positif dan signifikan terhadap kelelahan emosional guru SD. Hasil penelitian ini dapat menjadi pertimbangan bagi penyelia sekolah dan Kepala Dinas Pendidikan pada level pemerintah Kabupaten Boven Digoel dalam mengupayakan berbagai program yang berbeda untuk memperbaiki sistem pembebanan kerja dan iklim sekolah serta mendorong karakter guru yang suka bekerja keras dan pantang menyerah.Kata Kunci: beban kerja, karakteristik individu, iklim sekolah, kelelahan emosional, guru